Nye fund af »La Tène«-sværd i Sydvestjylland: Foreløbige betragtninger - Torfing, Tobias (Arkæologi i Slesvig-Archäologie in Schleswig, 2023)
During the last few years, several new swords of the La Tène-type have been found in Southwestern Jutland. They are, like most of the earlier finds, found in urn graves or firepit graves from the first century BC. This article presents three new finds from two locations, Erisvænget and Tjæreborg Nord, and puts them into their military and social contexts. The new finds expand our numbers of La Tène-swords in the region. Furthermore, the new finds are part of large excavations, and thus it is possible to relate the finds to the cultural landscape around them. The production, distribution, and use of the swords will be discussed. Analyses of one of the swords, from Tjæreborg Nord, and the metal analysis hint at a possible local production of La Tèneswords, though using foreign resources. Further, the article discusses why La Tène-type swords spread to the Germanic area at the very end of the period when the La Tène-swords were used. It seems that the swords do not signify a certain social class, but rather a new military development which is incorporated into a social network of relationships between people.